Kajian Yuridis Terhadap Ketentuan Wajib Helm Bagi Pengendara Sepeda Motor Berdasarkan Undang-Undang RI No. 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan - I Gede Ketut Suharta Yasa; Ni Made Rai Sukardi (Jurnal Ilmiah Raad Kertha, 2020)
This research is entitled, "Juridical Study of Mandatory Helmet Provisionsfor Motorcycle Riders Under Ri No. Law. 22 of 2009 Regarding Road Traffic andTransportation. "Problems discussed in this study are the Regulations and Criteria forthe mandatory use of Helmets for motorcyclists according to Law No. 22 of 2009concerning Road Traffic and Transportation and the constraints of mandatory helmetusers for cyclists excluded motorcycles. The writing method used in this study isNormative research. One of the fundamental changes in provisions in Law No. 22 of 2009concerning Traffic is obligatory for every motorcycle rider to wear a helmet with anIndonesian national standard (SNI). From the results of a study conducted by the authorabout the obligation of motorcyclists to be obliged to use helmets as regulated in article106 paragraph 8 of Act No. 22 of 2009 concerning Road Traffic and Transportationwhich is not effective where it should require all motorcyclists to use helmets . But it isindeed different for the Province of Bali because of the Governor's Decree of the Head ofthe Bali Region Number 217 of 1986 concerning the Requirement of the Use of a Helmetfor Motorbike Drivers and the person sitting behind him or on a bicycle in the BaliProvince I tolerate drivers motorbikes that use traditional Balinese clothing.